2017
DOI: 10.19166/pji.v12i1.383
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Pembelajaran Berbasis Masalah untuk Meningkatkan Ketrampilan Berpikir Kritis Siswa Kelas IX dalam Pelajaran Ekonomi [Problem-Based Learning Implementation to Increase Grade IX Students' Critical Thinking Skill in Learning Economics]

Abstract: This study aims to determine grade IX students' response to the application of problem-based learning in economy and to determine the increase students' critical thinking skills through problem learning methods. The design of this research is Class Research (TOD), with the subjects of 31 grade IX students at one Christian junior high school in the city of Tangerang. Research instruments used in the application of problem students' daily test scores, surveys, feedback from supervising teachers and fellow studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Many primary studies have been carried out in Indonesia to assess the PBL model's effect on junior high school students' critical thinking skills. Previous studies revealed that the implementation of PBL could enhance junior high school students' critical thinking skills (Arifin et al, 2015;Hakim et al, 2014;Ilham, 2018;Islahuddin et al, 2018;Marinda et al, 2018;Noer & Gunowibowo, 2018;Nurafiah et al, 2013;Putri & Fauzan, 2019;Sari et al, 2014;Sari et al, 2019;Sirait, 2019;Steven et al, 2019;Susanti & Suwu, 2016;Warmi, 2017;Waspadany et al, 2016;Yanti & Prahmana, 2017). However, the findings of the various studies are inconsistent, and the results in these studies do not yet include the value of the effect size of the PBL on students' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Many primary studies have been carried out in Indonesia to assess the PBL model's effect on junior high school students' critical thinking skills. Previous studies revealed that the implementation of PBL could enhance junior high school students' critical thinking skills (Arifin et al, 2015;Hakim et al, 2014;Ilham, 2018;Islahuddin et al, 2018;Marinda et al, 2018;Noer & Gunowibowo, 2018;Nurafiah et al, 2013;Putri & Fauzan, 2019;Sari et al, 2014;Sari et al, 2019;Sirait, 2019;Steven et al, 2019;Susanti & Suwu, 2016;Warmi, 2017;Waspadany et al, 2016;Yanti & Prahmana, 2017). However, the findings of the various studies are inconsistent, and the results in these studies do not yet include the value of the effect size of the PBL on students' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…So, it can be concluded the class that applies the problem-based learning model assisted by Edpuzzle is more effective to improve the students' critical thinking skills than the class that applies the expository learning model. Susanti (2016) argued that problem-based learning is a learning model that can develop the students' critical thinking skills through discussion in solving the problems presented. The result of the research explains that there is an increase in the students' critical thinking skills both in asking, answering, analyzing, and solving problems.…”
Section: Research Finding and Discussionmentioning
confidence: 99%
“…The research that linked to the problem-based learning model for improving the students' critical thinking skills is research conducted by Susanti (2016), who explained the problem-based learning makes a problem as the students' motivation to solve the learning problems. Also, the research of Silverajah & Govindaraj (2018) explained Edpuzzle provides a student-centred learning environment that appropriates the problembased learning and student-centred approach.…”
Section: Introductionmentioning
confidence: 99%
“…Siswa menyusun pengetahuan dengan cara membangun penalaran dari semua pengetahuan yang dimiliki sebelumnya dan dari semua yang didapat sebagai hasil kegiatan berinteraksi dengan sesama individu. Susanti, A. E, & Suwu, S. E. (2016) berpendapat bahwa Pembelajaran Problem Based Learning (PBL) adalah pembelajaran dapat mengembangkan keterampilan berpikir kritis siswa, melalui bertanya dan menjawab pertanyaan, menganalisis serta memecahkan permasalahan baik secara kelompok maupun pribadi. Sedangkan Hmelo-Silver & Barrows (2006) Kemampuan berpikir kritis pada pembelajaran matematika dapat dikembangkan di sekolah sampai perguruan tinggi.…”
Section: Problem Based Learningunclassified